SYSTEMATIC LITERATURE REVIEW (SLR) PEMANFAATAN MEDIA DALAM LAYANAN BIMBINGAN DAN KONSELING - sopian, asep amat (IKIP Siliwangi, 2022)
Guidance and counseling media is a tool used by guidance and counseling teachers in the form of software and hardware that serves as a tool in the activities of guidance and counseling services. The purpose of this systematic literature review is to find out and understand the use of media in guidance and counseling services. Research articles were obtained from two databases, namely DOAJ and ERIC. Literature search using the keywords media and counseling with the inclusion criteria of research articles from 2017-2021, primary articles, full text and research subjects are students. Of the 180 research articles, four articles were reviewed that met all the inclusion criteria and objectives of this literature review. Based on the results of this article review, the use of media is considered effective in the implementation of guidance and counseling services.